Natural Products and Cancer Drug Discovery 2017
DOI: 10.5772/67797
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi as Alternative and Reliable Sources for Potent Anticancer Agents

Abstract: In comparison with other natural sources like plants, highly diverse microorganisms are narrowly explored, especially with respect to their limitless potentials as repositories of exceptionally bioactive natural products. Of these organisms, fungi inhabiting tissues of plant in a noninvasive relationship (endophytic fungi) have proven undeniably useful and unmatchable as sources of potent bioactive molecules against several diseases such as cancer and related ailments. In general terms, endophytic fungi are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…24 Till date, many endophytes had been already reported that can produce bioactive compounds which are effective in anticancer assays. 25 The first and famous anticancer drug, Taxol, was produced from the endophytic fungus Taxomyces andreanae isolated from Taxus brevifolia Nutt that produce good anticancer activity against the cancer cell lines 26 . Figure 1 shows the recovering of fungal endophytes from plants and microscopic view of potent fungal endophyte.…”
Section: Importance Of Endophytes As a Source Of Cancer Drugsmentioning
confidence: 99%
“…24 Till date, many endophytes had been already reported that can produce bioactive compounds which are effective in anticancer assays. 25 The first and famous anticancer drug, Taxol, was produced from the endophytic fungus Taxomyces andreanae isolated from Taxus brevifolia Nutt that produce good anticancer activity against the cancer cell lines 26 . Figure 1 shows the recovering of fungal endophytes from plants and microscopic view of potent fungal endophyte.…”
Section: Importance Of Endophytes As a Source Of Cancer Drugsmentioning
confidence: 99%
“…Endemic species and plants at risk of extinction are among the most important hosts for revealing endophytes and their biotechnological potential (Omeje et al 2017). Thus, the identification of endophytic fungi from the Iridaceae species, K. brasiliensis, which is endemic to the Pampa biome, presents a promising option for uncovering fungi with the potential to produce antibacterial agents for further biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tan et al, they possess a resistance mechanism to overcome pathogenic invasion and are considered unmatchable "chemical synthesizers" acting as producers of a wide range of pharmacologically active substances (Tan and Zou, 2001). Their residency in the host plant for a substantial period prompts a constant chemical innovation with potentially reduced toxicity towards the host cells, notably eukaryotic cells, making them a unique resource notably for discovering anticancer molecules (Omeje et al, 2017). Following the discovery that the Food and Drug Administration approved anticancer agent Taxol, originally isolated from Taxus brevifolia, was also produced by endophytic fungi such as Taxomyces andreanae, numerous endophytes have been found to be producers of potent anticancer agents (Stierle et al, 1995;Kusari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%